TINGKAT KESUBURAN TANAH ULTISOL PADA LAHAN PERTAMBANGAN BATUBARA SANGATTA, KALIMANTAN TIMUR - Sudaryono, Sudaryono (Jurnal Teknologi Lingkungan, 2009)
Most of the land in East Kalimantan is ultisol soil types with low soil fertility. In a large-scaleland utisol used for oil palm, rubber and industrial plantations, but on a scale farmersbecause of economic constraints has led to the ground ultisol terkelolannya not well.In general, land in coal mining utisol in Sangatta, East Kalimantan has a low soil fertilitylevels in various limiting factors, such as: poor content of organic material, so as toimprove soil fertility with fertilizer needed organic fertilizer derived from compost ormanure. Cation exchange capacity values are quite high up (10,4-17,36 me/100 g), sothe land can only be used for the development of cash crops or plantation crops. Mostof the land in Sangatta acidic, with high Al saturation, to reduce the acidity of the soilcan be done by or with the accumulation Calcification phospat (element P) and KCl.